1996
DOI: 10.1073/pnas.93.22.12513
|View full text |Cite
|
Sign up to set email alerts
|

A tumor-selective somatostatin analog (TT-232) with strong in vitro and in vivo antitumor activity.

Abstract: We report a series of new in vitro and in vivo data proving the selective antitumor activity of our somatostatin structural derivative, TT-232. In vitro, it inhibited the proliferation of 20 different human tumor cell lines in the range of 50-95% and induced a very strong apoptosis. In vivo was not toxic at a dose of 120 mg/kg of b.w. in mice. Long-term incubation (24 h) of tumor cells with TT-232 caused significant inhibition of tyrosine kinases in good correlation with the apoptosis-inducing effect. The le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(63 citation statements)
references
References 34 publications
0
59
0
4
Order By: Relevance
“…Similarly, SST inhibits proliferation and migration of other cancer cells through downregulation of Akt and/ or ERK cascades (Pola et al, 2003;Sun et al, 2007). SST analogs result effective in vivo, inhibiting the growth of induced xenografts and animal tumors (Keri et al, 1996;Kahan et al, 1999), as well as counteracting the growth of neuroendocrine tumors, where they act by downregulating the ERK cascade (Hubina et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, SST inhibits proliferation and migration of other cancer cells through downregulation of Akt and/ or ERK cascades (Pola et al, 2003;Sun et al, 2007). SST analogs result effective in vivo, inhibiting the growth of induced xenografts and animal tumors (Keri et al, 1996;Kahan et al, 1999), as well as counteracting the growth of neuroendocrine tumors, where they act by downregulating the ERK cascade (Hubina et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike somatostatin or conventional somatostatin analogues, TT-232 does not inhibit growth hormone release or gastrin secretion in vivo (4) but it exerts a strong antiproliferative effect and selectively induces caspase-and Bcl-2-independent cell death in a large variety of tumor cells both in vitro and in vivo (4). We have shown previously that TT-232 acts trough seven-pass transmembrane somatostatin receptors to induce G 1 cell cycle arrest (5).…”
Section: Introductionmentioning
confidence: 99%
“…However the magnitude of inhibition of PTK activity is similar in all the three peptides (about 45-50% inhibition in PTK activity), in MCF-7 cells. Pawlikowski et al (1998) and Keri et al (1996) have demonstrated that somatostatin analogs mediate their anti-neoplastic effects by the inhibition of PTK activity, in several carcinomas. [34][35][36] The activation of protein tyrosine phosphatase, by SSTR2 has been recognized as one of the predominant signaling mechanisms mediating cell growth arrest (via SSTRs 1, 2, 4, or 5) or apoptosis (via SSTR3).…”
Section: Discussionmentioning
confidence: 99%